Bimetallic Ruthenium‐Cobalt Catalyst Supported on Carbon Nanotubes: Synthesis, Characterization, and Application in Electrochemical Sensing of Isoleucine - Omrüye Ozok Arıcı; Aykut Caglar; Bassam A. Najri; Nahit Aktaş; Arif Kivrak; Hilal Kivrak (Advanced Materials Interfaces)
Abstract In this work, a bimetallic Ru‐Co catalyst based on carbon nanotubes (Ru‐Co/CNT) with a Ru to Co ratio of 95:5 is developed. The catalyst, featuring a total metal loading of 3% on the CNTs, is synthesized using the NaBH4 reduction method. Several analytical analyses are used to detect the properties of the Ru‐Co/CNT catalyst. X‐ray diffraction (XRD) provides information on crystal structures of the catalysts, high‐resolution transmission electron microscopy (HR‐TEM) reveals particle size and distribution, inductively coupled plasma mass spectrometry (ICP‐MS) measures the elemental composition, and X‐ray photoelectron spectroscopy (XPS) use to investigate the chemical oxidation states. In addition, thermal techniques including temperature‐programmed reduction (TPR), temperature‐programmed oxidation (TPO), and temperature‐programmed desorption (TPD) are used to recognize the active sites on the catalyst's surface and the acidity. Then, the Ru‐Co/CNT catalyst is applied as a sensor for isoleucine amino acid for the first time. It shows high performance with these parameters, sensitivity (0.002 mA cm−2 mm), LOD – limit of detection (0.04 µm), and LOQ – limit of quantification (0.12 µm). Moreover, the interferences of common serum blood including (D‐glucose, uric acid, ascorbic acid, and L‐tryptophan) are studied. The findings indicated that the sensor is applicable to work in complex biological systems.